The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1155/2011/254724
|View full text |Cite
|
Sign up to set email alerts
|

The Many Forms and Functions of Long Term Plasticity at GABAergic Synapses

Abstract: On February 12th 1973, Bliss and Lomo submitted their findings on activity-dependent plasticity of glutamatergic synapses. After this groundbreaking discovery, long-term potentiation (LTP) and depression (LTD) gained center stage in the study of learning, memory, and experience-dependent refinement of neural circuits. While LTP and LTD are extensively studied and their relevance to brain function is widely accepted, new experimental and theoretical work recently demonstrates that brain development and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 97 publications
1
54
0
Order By: Relevance
“…These functions are implemented by inhibitory circuits, including excitatory synapses on GABAergic interneurons. These excitatory synapses on GABAergic interneurons show the spike time-dependent or Hebbian type of LTP, as reported previously (Lamsa et al, 2005;Sarihi et al, 2008, Perez et al, 2001; for review, see Maffei, 2011). This potentiation of inhibitory circuits may last for a long time.…”
Section: Functional Significance Of Ltp Of Inhibitory Synapses In Corsupporting
confidence: 72%
See 2 more Smart Citations
“…These functions are implemented by inhibitory circuits, including excitatory synapses on GABAergic interneurons. These excitatory synapses on GABAergic interneurons show the spike time-dependent or Hebbian type of LTP, as reported previously (Lamsa et al, 2005;Sarihi et al, 2008, Perez et al, 2001; for review, see Maffei, 2011). This potentiation of inhibitory circuits may last for a long time.…”
Section: Functional Significance Of Ltp Of Inhibitory Synapses In Corsupporting
confidence: 72%
“…LTP of GABAergic synaptic transmission has been extensively studied in the visual cortex (Komatsu and Iwakiri, 1993;Komatsu, 1994;Maffei et al, 2006), hippocampus (Grunze et al, 1996;McLean et al, 1996;Caillard et al, 1999;Gubelline et al, 2001;Patenaude et al, 2003), and other regions of the brain (for review, see Maffei, 2011). However, all of these studies, except for the one on brainstem dopamine neurons (Nugent et al, 2007), reported LTP of inhibitory synapses on pyramidal or excitatory principal neurons.…”
Section: Induction Of Ltp Of Inhibitory Synapses On Gabaergic Internementioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, activity-dependent plasticity of glutamatergic synapses, such as LTP and LTD, gained center stage in the study of learning, memory, and experiencedependent refinement of neural circuits (Maffei, 2011). Both LTP and LTD are extensively studied and their relevance to brain function is widely accepted, new experimental and theoretical work recently demonstrates that brain development and function relies on additional forms of plasticity, some of which occur at nonglutamatergic synapses (Maffei, 2011).…”
Section: Glutamatementioning
confidence: 99%
“…The expression and modification of synaptic proteins is dynamically regulated, depending on the neuronal activity. This process is called synaptic plasticity, and is thought to be the cellular basis of learning and memory (Bagal et al, 2005;Maffei, 2011;Martin & Morris, 2002). Plasticity-induced changes can occur on both sides of the synapse by altering Ca 2+ -dependent neurotransmitter release from the presynaptic nerve terminal and/or modifying the response to neurotransmitter in the postsynaptic neuron (Evans & Morgan, 2003).…”
Section: Introductionmentioning
confidence: 99%